Efficiency and Speculation in a Model with Price-Contingent Contracts - Svensson, Lars E. O. (Econometrica, 1981)
[This paper emphasizes the importance of endogenous (price) uncertainty as distinct from the standard exogenous uncertainty about the state of the world. Markets where agents can enter into forward contracts contingent upon future spot prices are studied with respect to existence of equilibrium, occurrence of speculation, and efficiency.]